If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7 + -2b) + 2(5b + 2) = 0 (7 * 4 + -2b * 4) + 2(5b + 2) = 0 (28 + -8b) + 2(5b + 2) = 0 Reorder the terms: 28 + -8b + 2(2 + 5b) = 0 28 + -8b + (2 * 2 + 5b * 2) = 0 28 + -8b + (4 + 10b) = 0 Reorder the terms: 28 + 4 + -8b + 10b = 0 Combine like terms: 28 + 4 = 32 32 + -8b + 10b = 0 Combine like terms: -8b + 10b = 2b 32 + 2b = 0 Solving 32 + 2b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 2b = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 2b = 0 + -32 2b = 0 + -32 Combine like terms: 0 + -32 = -32 2b = -32 Divide each side by '2'. b = -16 Simplifying b = -16
| -0.2x-0.3y=0.2 | | -x+5-3x=-55 | | 5x-35=x-13 | | 10x=15x-15 | | 8x-6=5x-12 | | 2(23-x-2y)+2(23-x-7)=20 | | 4(x+3)=3x+3 | | 2(x+2)=3x-4 | | 2v+4=-2(2v+4) | | -6-7(5k-7)=3k-11(1+4k) | | 0=2x^3+8x+1 | | y=392-47.5x | | (-2*-2*-2*-2)-3(6+7)= | | 10=2x+8x | | 2+5r=26 | | 3n+24= | | x+y+2z=23 | | -1+x=x+11 | | x+6=1+2x+8 | | 0.16(y-8)+0.10y=0.18y-0.09(10) | | 11(-7n+4)=-23-11n | | 1.5k+3.5=-4 | | -3x-24=-6x+33 | | 10(1-p)=10(p+9) | | 12u+17y=891 | | 36b-9=18b+3 | | 27-2x=x | | 5+2r=26 | | (3x+2y)2= | | 13xsquared+26x+14=0 | | -12+10x=9x+13 | | -22(x+1)=-11(x+2) |